Using Single-Photon Emission Computerized Tomography on Patients With Positive Quantitative Electroencephalogram to Evaluate Chronic Mild Traumatic Brain Injury With Persistent Symptoms - Gosset, Alexi; Wagman, Hayley; Pavel, Dan; Cohen, Philip Frank; Tarzwell, Robert; Bruin, Simon de; Siow, Yin Hui; Numerow, Leonard; Uszler, John; Rossiter-Thornton, John F.; McLean, Mary; Lierop, Muriel van; et al. (Frontiers in Neurology, 2022)
Background: Following mild traumatic brain injury (mTBI), also known as concussion, many patients with chronic symptoms (>3 months post injury) receive conventional imaging, such as computed tomography (CT) or magnetic resonance imaging (MRI). However, these modalities often do not show changes after mTBI. We studied the benefit of triaging patients with ongoing symptoms >3 months post injury using quantitative electroencephalography (qEEG) and then completing a Brain Single Positron Emission Computed Tomography (SPECT) to aid in diagnosis and early detection of brain changes. Methods: We conducted a retrospective case review of 30 outpatients with mTBI. Patients were assessed by a neurologist, consented and received a qEEG, and if the qEEG was positive they were consented and received a brain SPECT scan. The cases and diagnostic tools were collectively reviewed by a multidisciplinary group of physicians at biweekly team meetings including neurology, nuclear medicine, psychiatry, neuropsychiatry, general practice psychotherapy, neuro-ophthalmology, and chiropractic providers. The team noted the cause of injury, post injury symptoms, relevant past medical history, physical exam findings, diagnoses and commented on the patients’ SPECT scans. We then analysed the SPECT scans quantitatively using 3D-SSP software. Results: All patients had cerebral perfusion abnormalities demonstrated by SPECT but mostly undetectable with conventional imaging (CT/MRI). Perfusion changes were localized primarily in the cerebral cortex, basal ganglia and cingulate cortex, which correlated with the patients’ symptoms and exam findings. Qualitative and quantitative analysis yielded similar results. Most commonly, patients experienced persistent headache, memory loss, concentration difficulties, depression, and cognitive impairment post mTBI. Due to their symptoms, most patients were unable to return to their previous employment and activity level. Conclusion: Our findings outline the physical basis of neurological and psychiatric symptoms experienced by patients with mTBI. Increased detection of mTBI can lead to the development of improved targeted treatments for mTBI and its various sequelae.